Factors Influencing the Decision to Buy Green Products among Young Consumers in an Emerging Country - I Made Sukresna; Jesca Edward Mikina (Media Ekonomi dan Manajemen, 2024)
Environmental concerns have led to increased environmentally conscious practices and the production of green products. However, in an emerging country like Tanzania, young Tanzanian consumers have shown less responsiveness, necessitating an exploration of the factors influencing their purchase behaviour. This study investigates the factors influencing young Tanzanian consumers' decision to buy green products. A quantitative approach was conducted using structured online questionnaires to collect data from 161 individuals aged 18 to 35. The data is analysed using Partial Least Squares-Structural Equation Modeling. Results reveal that environmental consciousness and price perception positively influence green product awareness, while green advertising does not. Environmental consciousness exhibits a more significant influence over price perception. Subsequently, green product awareness positively influences green-product buying decisions. These findings indicate that young Tanzanian consumers know about green issues and are ready to pay more for green products. Businesses and policymakers can develop more effective strategies to promote sustainable behaviours and facilitate the transition to a greener economy. This study provides valuable insights into the critical factors driving the purchasing behaviour of green products among young consumers, emphasising the need for targeted efforts to encourage sustainable consumption in emerging economies.